Electrochemical Characterization of a New Biodegradable FeMnSi Alloy Coated with Hydroxyapatite-Zirconia by PLD Technique - Nicanor Cimpoeşu; Lucia Carmen Trincă; Georgiana Dascălu; Sergiu Stanciu; Silviu Octavian Gurlui; Daniel Mareci (Journal of Chemistry)
Biodegradable alloys are very attractive biomaterials. Electrochemical impedance spectroscopy (EIS) and linear potentiodynamic polarization (LPP) techniques were used for the study of the electrochemical behavior of uncoated FeMnSi and coated FeMnSi with hydroxyapatite + zirconia (HA-ZrO2) through pulsed laser deposition (PLD) technique. Experiments were carried out using Hank’s balanced salt solution (HBSS). It has been shown that in HBSS the impedance for uncoated FeMnSi was mainly characterized by one capacitive effect, which related to the alloy charge transfer control. The charge transfer resistance increases for HA-ZrO2-coated FeMnSi alloy. The equivalent circuits simulating the electrochemical behavior of both uncoated and HA-ZrO2-coated FeMnSi alloys in HBSS were proposed. From LPP the corrosion resistance was evaluated by means of the zero current potential (ZCP) and corrosion current density (jcorr). The surface morphology of both uncoated and HA-coated FeMnSi alloys in HBSS obtained after LPP was studied using scanning electron microscopy (SEM).